Freedom and Adaptive Preferences. - von Weizsäcker, Carl Christian. (The Graz Schumpeter Lectures, 2024)
Traditional welfare economics works with the assumption of the fully rational economic agent (homo economicus) whose preferences are fixed. To the contrary, this book presents a theory of welfare economics that maintains the principles of normative individualism while allowing for adaptive or changeable preferences.